2020
DOI: 10.2147/oarrr.s248750
|View full text |Cite
|
Sign up to set email alerts
|

<p>Treatment Patterns and Health Care Costs of Lupus Nephritis in a United States Payer Population</p>

Abstract: Objective: To describe the characteristics, treatment patterns, health care resource utilization (HCRU), and cost of care for members of a large United States (US) health insurance plan with lupus nephritis (LN). Methods: A retrospective observational study was conducted using a health insurance plan database to identify adult members with a diagnosis of LN. Medical and pharmacy claims were used to describe demographics, comorbidities, HCRU, and cost patterns over a 12month follow-up period for each patient, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 24 publications
0
29
1
Order By: Relevance
“…Our review from January 2000 to June 2020 identified 9224 abstracts for review; 479 full-text articles were selected for full-text review (Figure 1). Overall, 51 articles met selection criteria and captured the desired outcomes: health care utilization (28 articles), 10, drug utilization (20 articles), 11,24,[28][29][30][32][33][34][35]37,38,41,42,[47][48][49][50][51][52][53] adherence (7 articles), 27,49,51,52,[54][55][56] direct costs (20 articles), 10,11,20,22,24,25,[28][29][30][31][32][33][34][35]40,42,43,[57][58][59] and indire...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Our review from January 2000 to June 2020 identified 9224 abstracts for review; 479 full-text articles were selected for full-text review (Figure 1). Overall, 51 articles met selection criteria and captured the desired outcomes: health care utilization (28 articles), 10, drug utilization (20 articles), 11,24,[28][29][30][32][33][34][35]37,38,41,42,[47][48][49][50][51][52][53] adherence (7 articles), 27,49,51,52,[54][55][56] direct costs (20 articles), 10,11,20,22,24,25,[28][29][30][31][32][33][34][35]40,42,43,[57][58][59] and indire...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Among the 39 longitudinal studies included, the length of follow-up range was 6 months to 10 years, with the earliest study periods beginning in 1987. 10,11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45]47,48,51,53,[56][57][58][59][60]62,68,69 Across all studies, sample sizes varied from fewer than 100 patients up to 340,000 patients, depending on data source, study period, and study objectives. More than 60% of the articles had study populations that were more than 90% female.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations